Humans in automated decision-making under the GDPR and AI Act - Anna Levitina (Revista CIDOB d'Afers Internacionals)
Human oversight is a fundamental safeguard against inappropriate judgments made by machines about people who are the targets of these decisions. Although the General Data Protection Regulation (GDPR) and the AI Act address human oversight to some extent, they fall short in addressing qualitative aspects and the integration of human overseers into governance frameworks. This paper examines the legal requirements for human oversight, investigating how these intersect with the accountability obligations of the automated decision-making (ADM) deployers and individual rights. It argues for a more comprehensive approach that not only includes human oversight, but also a continuous and rigorous assessment of the effectiveness of human control. Without that, human oversight may fail to protect adequately and could even worsen the impact on individuals affected by ADM.